Atomic Layer Deposition of Titanium Silicate for Multi-Patterning Process - Lee, Sanghun; Seo, Seunggi; Noh, Wontae; Oh, Il Kwon; Kim, Hyungjun (2021 IEEE International Interconnect Technology Conference, IITC 2021, 2021)
We develop the atomic layer deposition (ALD) process of titanium silicate with halide-free precursor and evaluate film properties as a spacer for self-aligned double/quadruple patterning (SADP/SAQP). Growth characteristics are investigated depending on substrate temperature. Growth per cycle (GPC) at 100 °C is largely observed than the estimated value, while that as 200 °C shows an opposite trend. There have been reports on ALD ternary oxides, but different growth characteristics observed in this work have not been fully understood. In this work, the growth behavior of ALD titanium silicate are studied by correlating different characterization results, including infrared spectra, chemical compositions, and X-ray reflection spectra. Correlative results suggest that the surface density of hydroxyl group would be a key role for different growth characteristics of titanium silicates. Also, the feasibility of ALD titanium silicate as a spacer is evaluated, such as etch rates and deposited titanium silicates shows better quality than a conventional SiO2 spacer. This study on ALD titanium silicate should significantly expand multi-patterning applications, especially in a semiconductor field.
Keywords: Atomic layer deposition; Atomic layer deposition supercycle; Atomic-layer deposition; Deposition process; Growth characteristic; Multi patterning; Patterning process; SADP/SAQP; Titanium silicate; ALD supercycle; Atomic Layer Deposition (ALD); Growth characteristics; SADP/SAQP; Titanium silicate